Pengaruh Integritas, Kompetensi dan Skeptisme Auditor Terhadap Kualitas Audit - Syamsuri Rahim; Ratna Sari; Wardaningsi Wardaningsi; Muslim Muslim (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
The professionalism of auditors in carrying out attestation of financial statements prepared by partners has a very important role. This is because the results of the attestations that have been carried out by an auditor serve as a communication medium regarding the integrity of the performance carried out by the partners. Some things that are considered to have an influence on the professional attitude of an auditor in providing quality audit reports are the attitude of integrity, competence and skepticism when carrying out an attestation task. This study aims to determine the effect of integrity, competence and auditor skepticism on the quality of audit results at the Inspectorate of South Sulawesi Province. The data used in this study are primary data in the form of respondent's assessment of the integrity, competence and skepticism of auditors and the quality of audit results at the Inspectorate of South Sulawesi Province. Methods of data collection using questionnaires and literature study. The data analysis technique used multiple linear regression analysis, t test, F test and determination coefficient test. The results of the study found that the integrity and skepticism of auditors had a significant effect on the quality of audit results at the Inspectorate of South Sulawesi Province. Competence does not have a significant effect on the quality of audit results at the Inspectorate of South Sulawesi Province.